The polycystic ovary syndrome and the metabolic syndrome : a possible chronobiotic-cytoprotective adjuvant therapy - Spinedi, Eduardo J. (2018)
Fil: Spinedi, Eduardo J. Universidad Nacional de la Plata. Facultad de Ciencias Médicas. Centro de Endocrinología Experimental y Aplicada; Argentina